التطوير المهني لأعضاء هيئة التدريس : مدخل لتحقيق الجودة في التعليم الجامعي (Journal of Faculty of Education, 2021)
This study tackled the professional development of staff members in higher education institutions, with emphasis on the diverse roles of the staff members they are associated with the spirit of the currently accepted educational theories and thoughts.The study aimed to clarify the roles, tasks and competences of staff members in higher education institutions and the need and justifications of the importance of professional development. The study tried to find answers for a number of questions; the most important are: What are the roles, tasks and competencies of staff members? Why is it necessary to pay attention for the staff members' performance development? What are the competencies the teaching staff in these institutions should be equipped with? What are the means and patterns of training needed to develop competencies of the teaching staff members?The study adopted the descriptive analytical methodology by analyzing the views and ideas of experts on the topic. The study summed up with a number of conclusions and recommendations.
Keywords: التطوير المهني; الجودة في التعليم العالي; الكفايات; عضو هيئة التدريس بالجامعة